As modificações dos trajes juninos e sua interferência no processo coreográfico no município de Abaetetuba - OLIVEIRA, Stephanie Vaz (2018)
The present work proposes to analyze the transformations occurred in the June dresses in the municipality of Abaetetuba highlighting three periods: 2007, 2013 and 2016; and how these transformations influenced the choreography to change. The work aims to investigate the reasons for the modifications of the June Quadrille Costumes, and what influences these changes have had on the choreography since these three years. The methodology includes a bibliographical survey, an ethnographic record of the multiple cultural aspects involved in the event and interviews aimed to provide subsides into the process of transformation about costumes and choreography oh June. The authors that guided this research were Luciana CHIANCA (2007), Lenora LOBO and Cássia NAVAS (2008), Armindo BIAO (2009) and Paula OLIVEIRA (2015). From the initial phase of this research, I clearly understood the modifications about the June Quadrille suffered, as the questions belonging to this culture were abruptly changed by contemporaneity, becoming modernized, I understood that it is necessary to resignify of the culture, cause tends to change according to the place and year to which they are inserted.